Neurofilament results for the phase II neuroprotection study of phenytoin in optic neuritis. (7th November 2020) - Raftopoulos, R.; Kuhle, J.; Grant, D.; Hickman, S. J.; Altmann, D. R.; Leppert, D.; Blennow, K.; Zetterberg, H.; Kapoor, R.; Giovannoni, G.; Gnanapavan, S.
Abstract : Background: A randomized trial of phenytoin in acute optic neuritis (ON) demonstrated a 30% reduction in retinal nerve fiber layer (RNFL) loss with phenytoin versus placebo. Here we present the corresponding serum neurofilament analyses. Methods: Eighty‐six acute ON cases were randomized to receive phenytoin (4–6 mg/kg/day) or placebo for 3 months, and followed up for 6 months. Serum was collected at baseline, 3 and 6 months for analysis of neurofilament heavy chain (NfH) and neurofilament light chain (NfL). Results: Sixty‐four patients had blood sampling. Of these, 58 and 56 were available at 3 months, and 55 and 54 were available at 6 months for NfH and NfL, respectively. There was no significant correlation between serum NfH and NfL at the time points tested. For NfH, the difference in mean placebo – phenytoin was −44 pg/ml at 3 months ( P  = 0.019) and −27 pg/ml at 6 months ( P  = 0.234). For NfL, the difference was 1.4 pg/ml at 3 months ( P  = 0.726) and −1.6 pg/ml at 6 months ( P  = 0.766). Conclusions: At 3 months, there was a reduction in NfH, but not NFL, in the phenytoin versus placebo group, while differences at 6 months were not statistically significant. This suggests a potential neuroprotective role for phenytoin in acute ON, with the lower NfH at 3 months, when levels secondary to degeneration of the anterior visual pathway are still elevated, but not at 6 months, when levels have normalized. Abstract : Phenytoin treatment in acute optic neuritis demonstrates a reduction in serum NfH levels at 3 months, but not in NfL.